Success with traditional water conservation techniques - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
A silent revolution is taking place on Burkina Faso's Central Plateau. Thousands of planting pockets or zai, stone lines, permeable stone dams and straw mulch are transforming crop production as farmers see the benefits of using traditional farming...